2016
DOI: 10.1186/s40104-016-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in intercellular junctions and Kv channels in the intestine of piglets during the suckling and post-weaning periods

Abstract: BackgroundThe intestinal epithelium is an important barrier that depends on a complex mixture of proteins and these proteins comprise different intercellular junctions. The purpose of this study was to investigate the postnatal and developmental changes in morphology, intercellular junctions and voltage-gated potassium (Kv) channels in the intestine of piglets during the suckling and post-weaning periods.ResultsSamples of the small intestine were obtained from 1-, 7-, 14-, and 21-d-old suckling piglets and pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 47 publications
6
68
1
3
Order By: Relevance
“…The results from the present study confirmed that piglet growth performance, including ADFI, was enhanced with the increase in post‐weaning time (Wang et al, ; Xiccato, Trocino, Sartori, & Queaque, ). The SCFAs, mostly acetate, propionate and butyrate, are produced via the fermentation of dietary carbohydrates and proteins in the colon (Parrett et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The results from the present study confirmed that piglet growth performance, including ADFI, was enhanced with the increase in post‐weaning time (Wang et al, ; Xiccato, Trocino, Sartori, & Queaque, ). The SCFAs, mostly acetate, propionate and butyrate, are produced via the fermentation of dietary carbohydrates and proteins in the colon (Parrett et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…This drop is reflected in a concomitantly increased permeability for FD-4 and HRP. Previous studies showed lower abundances of occludin mRNA and protein, claudin-3 protein, and increased lactulose permeability after weaning [50, 76]. Thus artificial rearing induced a similar response as seen after conventional weaning.…”
Section: Discussionsupporting
confidence: 57%
“…Third, microscopes were used to observe the samples, and computer-aided systems were used to photograph the samples. Finally, an image analysis system was used to measure villi length and crypt length [23,24].…”
Section: Animal Management and Samplementioning
confidence: 99%